Morphological changes of Paulownia seedlings infected phytoplasmas reveal the genes associated with witches' broom through AFLP and MSAP. - Xibing Cao; Guoqiang Fan; Zhenli Zhao; Minjie Deng; Yanpeng Dong (PLoS ONE)
Paulownia witches' broom (PaWB) caused by phytoplasma might result in devastating damage to the growth and wood production of Paulownia. To study the effect of phytoplasma on DNA sequence and to discover the genes related to PaWB occurrence, DNA polymorphisms and DNA methylation levels and patterns in PaWB seedlings, the ones treated with various concentration of methyl methane sulfonate (MMS) and healthy seedlings were investigated with amplified fragment length polymorphism (AFLP) and methylation-sensitive amplification polymorphism (MSAP). Our results indicated that PaWB seedlings recovered a normal morphology, similar to healthy seedlings, after treatment with more than 20 mg · L-1 MMS; Phytoplasma infection did not change the Paulownia genomic DNA sequence at AFLP level, but changed the global DNA methylation levels and patterns; Genes related to PaWB were discovered through MSAP and validated using quantitative real-time PCR (qRT-PCR). These results implied that changes of DNA methylation levels and patterns were closely related to the morphological changes of seedlings infected with phytoplasmas.